C1EIP Functions as an Activator of ENO1 to Promote Chicken PGCs Formation via Inhibition of the Notch Signaling Pathway - Jin, Kai; Li, Dong; Jin, Jing; Song, Jiuzhou; Zhang, Yani; Chang, Guobing; Chen, Guohong; Li, Bichun (Frontiers in Genetics, 2020)
The production of germ cells, especially primordial germ cells (PGCs), is important for avian stem cells and reproduction biology. However, key factors involved in the regulation of PGCs remain unknown. Here, we report a PGC-related marker gene: C1EIP (Chromosome 1 Expression in PGCs), whose activation and expression are regulated by the transcription factor STAT3 (signal transducer and activator of transcription 3), histone acetylation, and promoter methylation. C1EIP regulates PGCs formation by mediating the expression of PGC-associated genes, such as CVH (Chicken Vasa Homologous) and CKIT (Chicken KIT proto-oncogene). C1EIP knockdown during embryonic development reduces PGC generation efficiency both in vitro and in ovo. Conversely, C1EIP overexpression increases the formation efficiency of PGCs. C1EIP encodes a cytoplasmic protein that interacts with ENO1 (Enolase 1) in the cytoplasm, inhibits the Notch signaling pathway, and positively regulates PGC generation. Collectively, our findings demonstrate C1EIP as a novel gene involved in PGC formation, which regulates genes involved in embryonic stem cell differentiation through interaction with ENO1 and subsequent inhibition of the Notch signaling pathway by the impression of Myc (MYC proto-oncogene).